O tradutor intérprete de libras no teatro: a construção de sentidos a partir de enunciados cênicos - Fomin, Carolina Fernandes Rodrigues (2018)
The present research aims to observe sign language translator and interpreter (SLI) activity in artistic-cultural sphere, during interpretative act at theatrical spectacle genre, describing and analyzing the nonverbal, verbal and verbal-visual elements that mark this professional’s enunciation during discursive mobilization of a theatrical scene that carries Portuguese language utterances into the Brazilian sign language (libras). To do so, we performed a analytical-descriptive qualitative study of four spectacles that took place in São Paulo and had their presentations accessible in libras, they were: Hotel Mariana (07/05//2017), Ida (15/08/2017) and Adeus palhaços mortos! (08/22/2017) at Instituto Itaú Cultural, and A princesinha medrosa (09/03/2017) at SESC Santana. In addition to the video recording of the shows and the performance of the SLIs, this study corpus was formed by the questionnaire we developed and that was applied to the SLIs, the response to the questionnaires and the spectacles flyers. The questions that motivated this research were: a) Beyond the text spoken by the actors, what aspects of theatrical scene influence the enunciation of the SLI during the interpretative act? b) What are the strategies used by SLI to communicate extralinguistic aspects? c) Preparation and the logistics of acting as position and vision of the theatrical scene influence the interpretive strategies of SLIs? Our theoretical basis was from the dialogue between studies on theatricality, sign language translation interpretation studies and the dialogical perspective of the Bakhtin’s Circle on language. In this study, that we consider utterances by its extraverbal, verbal and verbal-visual dimension, we observe the sociohistorical- ideological context and understand the theatrical scene as a verb-visual utterance that occurs in the plot of texts composed both by what was said by the actors, as by the stage, stage movement, stage elements, projections, sound effects, etc. The analysis of nonverbal, verbal and verbal-visual elements highlighted different ideological and enunciate positions and different interpretive choices depending on these variables. The corpus analysis points to a verbal-visual totality and how SLI influences and is influenced by the scene, in which is an amalgamated and constitutive element of the spectacle totality, of the concrete utterance